Adolescents' Knowledge, Attitude and Utilization of Emergency Contraceptive Pills in Nigeria's Niger Delta Region - Olayinka A. Onasoga, MSc., FWACN; Joel Adeleke Afolayan, PhD, FWACN; Tariebi Florence Asamabiriowei, BNSc; Umar Nda Jibril, PhD, FWACN; Abubakar Ayinla Imam, MSc, FWACN (Global Health and Education Projects, Inc., 2016)
Background and Objective: Risky sexual activity among adolescents is on the increase and contraceptive prevalence rate is low which is evidenced by high rate of teenage pregnancy in Bayelsa state, Nigeria. This study assesses the adolescents' knowledge, attitude and utilization of emergency contraceptive pills (ECP) in Amassoma Community, Bayelsa State, in the Niger Delta region of Nigeria. Methods: The study was a descriptive cross-sectional research design. A purposive sampling technique was used to select a sample of 220 respondents from the target population. Data were collected using a self-structured questionnaire. Descriptive and inferential statistics were used to analyze the data generated. Results: Majority of the respondents had high level of knowledge and positive attitude towards emergency contraceptive pills but had low level of utilization. Concerns about what others may say, parental attitude, contraceptive availability, contraceptive accessibility, and peer infl uences were the major factors that infl uenced the utilization of contraceptive pills. There was no signifi cant relationship between knowledge and utilization of emergency contraceptive pills, as well as level of knowledge and their utilization of emergency contraceptive pills. Conclusions and Global Health Implications: Adolescents in the study were more likely to use emergency contraceptive pills, if parents and others reaction to adolescents' contraceptive use were positive about those. Health care professionals, especially nurses, should organize enlightenment programs to educate adolescents, parents and the public on the benefi ts of adolescents' contraceptives use, especially ECP. Key words: Knowledge • Family Planning • Attitude • Utilization • Adolescents • Emergency Contraceptive Pills Copyright © 2016 Onasoga et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.